Prototype of FPGA Dynamic Reconfiguration Based-on Context-Oriented Programming - Ohkawa, Takeshi; Tanigawa, Ikuta; Sato, Mikiko; Hisazumi, Kenji; Ogura, Nobuhiko; Watanabe, Harumi (2019 IEEE 13th International Symposium on Embedded Multicore/Many-core Systems-on-Chip (MCSoC), 2019)
Acceleration by FPGA is expected for real-time edge processing as well as server applications in the cloud. A robot is one of the examples which need the acceleration of processing such as image recognition processing and actuation based on its visual feedback. As the system is more complex, it is required to introduce a management mechanism of FPGA dynamic reconfiguration. In this paper, we propose a method of system development which includes FPGA acceleration. The key idea of the proposed method is the FPGA reconfiguration based on a context, which is defined in Context-Oriented Programming (COP). This idea contributes to solve the cross-cutting concern problem at runtime. The problem causes to decrease the efficiency of development. Thus, this idea makes easily manage to FPGA reconfiguration with software in case of changing a whole system. In evaluation, we compare the reconfiguration time of FPGA to switch a context with the context switching time of the COP software written in C++ language. It indicates that the proposed method is feasible to handle FPGA context.